Variasi Diameter Lilitan Kawat Motor Induksi - Yudhi Agussationo; Sepdian; Puspita Ayu Armi (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2020)
Testing of 3 phase induction motors with a variety of wire diameters. First, find out the ideal wire size on an induction motor. Second, ratio of the power used on an induction motor with different winding wire sizes. Third, to find out the torque produced by an induction motor with different wire winding sizes. Then, The induction motor test was performed by taking the power data used on two motors with a diameter of 0.6 mm and 0.5 mm winding wire, RPM data and torque produced by an induction motor with a diameter of 0.6 mm and 0.5 mm. So, we can get the results the induction motor with a diameter of 0.6 mm wire uses as maximum power of 549.10 Watt or more than the induction motor with a diameter of a wire wound of 0.5 mm which only uses a maximum power of 345.95 Watt, the wire diameter induction motor winding 0.6 mm produces a maximum torque of 746.92 Nm or greater than an induction motor with a diameter of 0.5 mm winding wire which only produces a maximum torque of 383.97 Nm. So, It can be conclude that the more number of revolutions per minute (RPM), the torque produced will be smaller, then, the greater the torque produced, the more power is used.